On Optimum Tariff Structures - de V. Graaff, J. (Review of Economic Studies, 1949)
Journal Article On Optimum Tariff Structures Get access J. de V. Graaff J. de V. Graaff Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 1, 1949, Pages 47–59, https://doi.org/10.2307/2295788 Published: 01 April 1949